Use of children in political conflicts in Egypt: Legal categorization under international and national legislation - Abadir, Sandy Heshmat Shinouda (AUC Knowledge Fountain, 2016)
Children have been used during the so called Arab Spring in the Arab countries since 2011 as tools at the hands of different group of people to achieve certain benefits. In Egypt particularly during and after the 25th of January Revolution, this phenomenon became obvious where the Egyptian children have been used during demonstrations by revolutionaries, political factions, the state itself or even by their families. Each group uses children to achieve its own interests. Revolutionaries and security forces used them as human shields, whereas political faction especially Muslim brotherhood used them to wear the death shrouds during the sit-ins. Moreover, some families rented their children to participate in these sit-ins and receive money in return. In most of the cases, the children’s abusers or exploiters achieve certain gain whether it is financial or political gain. The families who rented their children got money and those who used them as human shields during demonstrations protected themselves from the opposite side. In this thesis, the use of children in political conflicts will be analyzed in lights of international and national legislation. This thesis argues that the children who have been used as tools during political conflicts in Egypt is considered to be victims of trafficking thus a new form of trafficking is recommended to be added to the Egyptian law. It further argues that the international and national legislation represented by the United Nations Convention on the Rights of the Child (UNCRC) and the Egyptian Child Law fail to properly categorize using children in political conflicts as form of trafficking although they both contain articles related to trafficking in persons. On the other hand, this thesis argues that both legislation, the UNCRC and the Egyptian Child Law legally categorize using children in political conflicts as form of violence against those children.